Humanistic care ability and its influencing factors among Chinese surgical nurses - Xiao‐Ju Teng; Miao‐Miao Yan; X. U. Yan‐Qun; L. I. Yuan‐Zheng; Xiu‐Bin Tao; Wei‐Zhen Zou; Xiao‐Ming Wang; Wenru Wang; Ying Jiang (Wiley, 2024)
Abstract Aim This paper aims to investigate the humanistic care ability among surgical nurses in China and identify its statistically significant influencing factors. Design A cross‐sectional, descriptive and correlational design was used. Methods A total of 210 surgical nurses were recruited from a tertiary public hospital in Wuhu, Anhui Province. Four with incomplete responses were excluded, leaving 206 participants for data analysis. Variables were measured using the general questionnaire, caring ability inventory (CAI), and General Self‐Efficacy Scale (GSES). Multivariate linear regression analyses were performed to identify the statistically significant influencing factors of participants' humanistic caring ability. Results The overall average score of the CAI was 190.14 (SD = 19.24), and the average scores for the three dimensions of cognitive, courage, and patience were 70.46 (SD = 7.77), 62.12 (SD = 8.47) and 57.56 (SD = 6.02), respectively. The overall average score of the GSES was 26.05 (SD = 5.77). Professional attitude, perceived care from the department head nurse, perceived care from colleagues and self‐efficacy were the statistically significant factors influencing the humanistic care ability of surgical nurses (R2 = 0.45, adjusted R2 = 0.44, F = 40.64, p < 0.001).